2022
DOI: 10.1051/0004-6361/202142049
|View full text |Cite
|
Sign up to set email alerts
|

Maximum luminosities of normal stripped-envelope supernovae are brighter than explosion models allow

Abstract: Context. Stripped-envelope supernovae (SE SNe) of Type Ib and Type Ic are thought to be the result of explosions of massive stars that have lost their outer envelopes. The favored explosion mechanism is via core-collapse, with the shock later revived by neutrino heating. However, there is an upper limit to the amount of radioactive 56Ni that such models can accommodate. Recent studies in the literature point to a tension between the maximum luminosity from such simulations and the observations. Aims. We used a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 55 publications
0
8
1
Order By: Relevance
“…Ni mass than the models mentioned above. Indeed, Ertl et al (2020) and Woosley et al (2021, who recomputed the light curves of Ertl et al 2020 with a better treatment of the radiation transport) reported that a substantial fraction of observed SE SNe is more luminous than their brightest models, while Sollerman et al (2022) found that 36% of the SNe Ib/Ic in their sample are brighter than the maximum r-band brightness predicted by models of Woosley et al (2021). Given that numerical models seem to underestimate the peak luminosities of SE SNe, the use of the Khatami & Kasen (2019) relation and the meanβ values computed with these models could, on average, overestimate the 56 Ni masses of SE SNe.…”
Section: Introductionmentioning
confidence: 99%
“…Ni mass than the models mentioned above. Indeed, Ertl et al (2020) and Woosley et al (2021, who recomputed the light curves of Ertl et al 2020 with a better treatment of the radiation transport) reported that a substantial fraction of observed SE SNe is more luminous than their brightest models, while Sollerman et al (2022) found that 36% of the SNe Ib/Ic in their sample are brighter than the maximum r-band brightness predicted by models of Woosley et al (2021). Given that numerical models seem to underestimate the peak luminosities of SE SNe, the use of the Khatami & Kasen (2019) relation and the meanβ values computed with these models could, on average, overestimate the 56 Ni masses of SE SNe.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 0.2 M e of 56 Ni is at the upper limit of the total amount of radioactive nickel produced in a neutrino-driven explosion; however, it is still within the range of accepted uncertainties (Ertl et al 2016;Sukhbold et al 2016;Ertl et al 2020). Moreover, if there is any asymmetry in the SN ejecta, the effective 4π-equivalent mass of 56 Ni might be higher (Kozyreva et al 2022;Sollerman et al 2022).…”
Section: Input Model and Methodsmentioning
confidence: 97%
“…Much earlier, Jacoby et al (1992) termed the underestimation of uncertainties in extragalactic distances to be a 'major embarrassment', while Rowan-Robinson (1985, 1988 called it 'incredible'. Overestimation of reliability of SNe Ia as a precise extragalactic distance indicator is also highlighted by Rowan-Robinson (2002 and Sollerman et al (2022).…”
Section: Introductionmentioning
confidence: 97%